2005
DOI: 10.1039/b500182j
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial death comes full circle: targeting plasmid replication in drug-resistant bacteria

Abstract: It is now common for bacterial infections to resist the preferred antibiotic treatment. In particular, hospital-acquired infections that are refractory to multiple antibiotics and ultimately result in death of the patient are prevalent. Many of the bacteria causing these infections have become resistant to antibiotics through the process of lateral gene transfer, with the newly acquired genes encoding a variety of resistance-mediating proteins. These foreign genes often enter the bacteria on plasmids, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…However, the knowledge that some plasmid types are prevalent in resistant bacterial populations could be useful to explore the possibility of identifying drugs targeting these plasmid families as a medicinal strategy for the treatment of drug-resistant bacteria. An antiplasmid approach has already been proposed, based on small molecules targeting specific replication control mechanisms, inducing plasmid elimination (28). The antiplasmid approach may one day rejuvenate those antibiotics that are no longer effective due to the prevalence of specific resistance plasmid families, enabling them to be effective once again.…”
Section: Targeting Plasmids Among Enterobacteriaceae-concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the knowledge that some plasmid types are prevalent in resistant bacterial populations could be useful to explore the possibility of identifying drugs targeting these plasmid families as a medicinal strategy for the treatment of drug-resistant bacteria. An antiplasmid approach has already been proposed, based on small molecules targeting specific replication control mechanisms, inducing plasmid elimination (28). The antiplasmid approach may one day rejuvenate those antibiotics that are no longer effective due to the prevalence of specific resistance plasmid families, enabling them to be effective once again.…”
Section: Targeting Plasmids Among Enterobacteriaceae-concluding Remarksmentioning
confidence: 99%
“…These criteria are best met by traits concerned with plasmid maintenance, especially replication controls (28). In 1971, Hedges and Datta proposed a plasmid classification scheme based on the stability of plasmids during conjugation, a phenomenon called plasmid incompatibility (27,47).…”
mentioning
confidence: 99%
“…These criteria are best met by traits concerned with plasmid maintenance, especially replication controls (DeNap and Hergenrother, 2005). In 1971 Datta and Hedges proposed a plasmid classification scheme based on the stability of plasmids during conjugation, a phenomenon called plasmid incompatibility (Datta and Hedges, 1971).…”
Section: Detection and Classification Of Plasmids Carrying Esbl And/omentioning
confidence: 99%
“…For example, it has been suggested that small molecules that disrupt the TA interaction would free the toxin to kill the host (11)(12)(13). However, both the identity and prevalence of TA systems in pathogenic bacteria are unknown.…”
mentioning
confidence: 99%